Організовані переселення за межі Української РСР у другій половині 1950-х – середині 1980-х рр. - Жбанова, К. (Сiверянський лiтопис, 2015)
У статті йдеться про трудові переселення з Української РСР до Російської РФСР та Казахської РСР у другій половині 1950-х – середині 1980-х рр. Розглянуто особливості державного регулювання в сфері міграції населення, створення та функціонування владних структур, що здійснювали переміщення людей за межі України. Досліджено систему пільг, якою користувалися переміщені родини, та визначено причини труднощів закріплення переселенців на нових місцях проживання. Проаналізовано соціально-економічні, демографічні та культурні наслідки перерозподілу трудових ресурсів в Україні, який проводився у другій половині 1950-х – середині 1980-х рр. В статье идет речь о трудовых переселениях с Украинской ССР в Российскую СФСР и Казахскую ССР во второй половине 1950-х – средине 1980-х гг. Рассмотрены особенности государственного регулирования в сфере миграции населения, создания и функционирования правительственных структур, осуществлявших перемещение людей за пределы Украины. Исследована система льгот, которой пользовались перемещенные семьи, и определены причины трудностей закрепления переселенцев на новых местах проживания. Проанализированы социально-экономические, демографические и культурные последствия перераспределения трудовых ресурсов в Украине, которое проводилось во второй половине 1950-х – средине 1980-х гг. The scientific study of the history of labor, employment, migration in search of work helps to better understand the history of Ukraine as a whole. The article deals with the problem of labor migration from the Ukrainian SSR to the Russian SFSR and Kazakhstan SSR in the second half of the 1950s – mid 1980s. Features of state regulation of migration, creation and operation of the authorities that carried out the movement of people from Ukraine are researched. The system of privileges for families that were resettlement is determined. The social, economic, demographic and cultural consequences of redistribution of labor resources in Ukraine, which was held in the second half of 1950 – mid 1980s, are analyzed. The material is based on archival sources, with rich factual materials that allows us to understand the essence of the process of resettlement working population in Soviet era. The author comes to the conclusion that, unlike the organized resettlements of the Second World War and the first post-war years, the movement that began in the second half of 1950th was voluntary and has relied on the economic policies of the Soviet regime, but not without taking into account national specific regions where conducted. The main feature of these migrations was organized character of relocation and resettlement of newcomers. In the regions which were left by settlers the government policy has led to spraying the local population and ultimately has caused population losses. Ukrainians in other Soviet republics lived in an artificial environment that was created by the state. Thus, in new places of residence was implemented leveling of national identity.